2016
DOI: 10.1371/journal.pone.0162468
|View full text |Cite|
|
Sign up to set email alerts
|

Time-Course of Changes in Choroidal Thickness after Complete Mydriasis Induced by Compound Tropicamide in Children

Abstract: PurposeThe aim of this study was to investigate the time-course of changes in choroidal thickness (ChT) following complete mydriasis induced by compound tropicamide.MethodsChT was measured by OCT with the enhanced-depth imaging technique (Spectralis HRA+OCT, Heidelberg Engineering, Germany) at nine locations of the fundus: subfoveal ChT (SFChT) and ChT at 1 mm and 3 mm from the fovea in four quadrants. Mydriasis was induced with compound tropicamide (0.5% tropicamide plus 0.5% phenylephrine hydrochloride, thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
(44 reference statements)
3
15
0
Order By: Relevance
“…During the mydriasis induced by topical use of muscarinic antagonists, both the thickness and curvature of the lens decrease, the anterior chamber depth increases and the axial length decreases in humans 21 23 , resulting in a hyperopic shift of the eye. Changes in choroidal thickness (ChT) during the topical administration of muscarinic antagonists was also observed in previous studies of human trials 21 , 24 26 with some studies reporting a thickening choroid 21 , 26 and others demonstrating a thinning choroid 24 , 25 . These results indicate that posterior segment of the eye undergoes dimensional changes after treatment with muscarinic antagonists, which may contribute to the refractive changes during the mydriasis.…”
Section: Introductionsupporting
confidence: 57%
“…During the mydriasis induced by topical use of muscarinic antagonists, both the thickness and curvature of the lens decrease, the anterior chamber depth increases and the axial length decreases in humans 21 23 , resulting in a hyperopic shift of the eye. Changes in choroidal thickness (ChT) during the topical administration of muscarinic antagonists was also observed in previous studies of human trials 21 , 24 26 with some studies reporting a thickening choroid 21 , 26 and others demonstrating a thinning choroid 24 , 25 . These results indicate that posterior segment of the eye undergoes dimensional changes after treatment with muscarinic antagonists, which may contribute to the refractive changes during the mydriasis.…”
Section: Introductionsupporting
confidence: 57%
“…; Li et al. ,b). It is found that the change of a relative peripheral myopic defocus after OK lens wear in most myopic eyes might act as a possible mechanism for myopia control (Kang & Swarbrick ), but the underlying mechanism is stilled unknown.…”
Section: Discussionmentioning
confidence: 99%
“…; Li et al. ,b). However, as observed in current and previous studies, great individual variation in response exists (Cho & Cheung ; Swarbrick et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, we have to take into consideration that the choroid has intrinsic dynamic changes that can influence its thickness. CT variation upon mannitol infusion [42], mydriasis induced by tropicamide [43], single administration of coffee [12], after water drinking tests [7], and after hemodialysis [18, 19] has already been reported. Also, studies have shown that the choroid can change its volume and thereby its thickness over a few days by five possible mechanisms [32]: changes in osmotic gradient [44], changes in vascular permeability [45], shift of aqueous humor flow from the anterior chamber to the choroid [46], moving retinal fluid across the retinal pigment epithelium into the choroid [47], and changes in the tonus of nonvascular smooth muscle cells that are controlled by both sympathetic and parasympathetic inputs [48].…”
Section: Discussionmentioning
confidence: 99%